RASIONALITAS PENGGUNAAN ANTIPSIKOTIK PADA PASIEN SKIZOFRENIA DI INSTALASI RAWAT INAP JIWA RSD MADANI PROVINSI SULAWESI TENGAH PERIODE JANUARI-APRIL 2014 - Fahrul, Fahrul; Mukaddas, Alwiyah; Faustine, Ingrid (Natural Science: Journal of Science and Technology, 2014)
Schizophrenia is a severe mental disorder, that antipsychotics was effective therapy to treat it. There are 50 million sufferers in the world, 50% did not receive appropriate treatment and  90% of patients who did not receive the proper treatment  in developing country. This research is aimed to find out rationality of antipsychotic usage includes right indication, drug, patient, dosage, and frequency in Schizophrenia Patient Department of Mental health in Madani Hospital of Central Sulawesi, in the period of January-April 2014. This research is a descriptive study, prospectively done by collecting primary data which was observation and interview, and secondary data was from the schizophrenia patient medical record.  Data analysis was done by descriptive quantitative to provide an overview of the characteristic of each study variables including patient characteristic, clinical characteristic, and rational use of drug. The obtained results in rationality treatment was as follows : 100% precise indications, 90.4% right drug, 87.8% right patient, 81.6% right dosage and 90.4% appropriate frequency of antipsychotic use.  Antipsychotic usage in schizophrenia Patient at mental health department of Madani Hospital of Central Sulawesi cannot be stated as rational yet.